Prevalence of virological failure and associated factors among adult individuals on highly active antiretroviral treatment (HAART) in public health facilities at Tulu Bolo Town, Southwest Shoa, Ethiopia, 2024 - Lamesa, Ashenafi; Teshoma, Shibire; Oljira Desta, Habtamu; Regassa, Belay Tafa; Waqkene, Tolossa (Frontiers in Public Health, 2025)
IntroductionThe goal of antiretroviral therapy for HIV infection is to achieve and maintain virological suppression. Review of charts of adult HIV-positive patients at public health facilities in Tulu Bolo Town reveals that approximately 6.07% of patients did not respond to first-line antiretroviral medication. The identified gap indicates that the study area’s virological failure prevalence and contributing factors are not well-documented. Thus, this study’s objectives are to evaluate prevalence and close a knowledge gap about factors associated with virological failure.ObjectiveThe objective of this study was to assess the prevalence of virological failure and associated factors among patients taking highly active antiretroviral therapy in Tulu Bolo Town Health facilities, Oromia, Ethiopia, 2024.MethodsHealth facility-based cross-sectional study was conducted at Tulu Bolo Town in public health facilities from 30 September 2024 to 30 October 2024. The total sample sizes of 274 records of clients were selected using simple random sampling technique. Data were cleaned and entered into EPI info version 7.2.0.1 and exported to SPSS version 20.0 for further analysis. The association was identified using binary logistic regression model. An adjusted odds ratio with 95% confidence intervals (CI) was computed to identify the presence and strength of association. Finally, statistically significant variables were declared at a p-value of < 0.05 along with 95% CI.ResultsA total of 274 charts of HIV-positive clients were included in the study. The magnitude of virological failure was 12.8% (95%CI 9, 17%). Baseline CD4 count < 200 (AOR 6.1, 95%CI 2.06, 18.43), clients infected with TB (AOR 4.8 95%CI 1.78, 12.96), treatment interruption (AOR 3.05, 95% CI 1.06, 8.77), and adherence (AOR 3.67, 95%CI 1.39, 9.66) were statistically significant association.Conclusion and recommendationThe overall prevalence of virological failure of this study was high as compared to standard. Baseline CD4 count, TB infection, treatment interruption, and adherence were significant factors. Health facility ART provider and HIV/AIDS program manager should give special attention for clients with history of TB co-infection and CD4 count < 200 needs care and support and providing TB preventive therapy.